Metodologi Ibn Abi Ḥātim dalam Kitab ‘Ilal al-Ḥadīṡ: Methodology of Compiling the Book of 'Ilal al-Ḥadīṡ by Ibn Abi Ḥātim - Arfan, Arfan; Alwi, Zulfahmi; Andi Darussalam; A., Nur Afni (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2024)
The Book of ‘Ilal al-Ḥadīṡ by Ibn Abi Ḥātim is one of the reference books that is widely discussed by hadith scholars. This research focuses on examining and analyzing the methodology used by Ibn Abi Ḥātim in the book. This research is descriptive qualitative research. Data was obtained and compiled from various sources, especially The Book of ‘Ilal al-Ḥadīṡ itself as well as other relevant scientific books and articles. All data obtained was reviewed and analyzed using a content analysis approach for further conclusions to be drawn. The results of this research found that Ibn Abi Ḥātim was one of the great scholars of the 4th century who had significant contributions in many fields of Islamic science. The Book of ‘Ilal al-Ḥadīṡ is one of Ibn Abi Ḥātim's monumental works which has become an important reference for hadith scholars. This research also found that the number of hadiths that were the object of study in the book was 2840 hadiths. Ibn Abi Ḥātim not only adhered to personal opinions in analyzing illat hadith but also referred to the opinions of his father Abu Hatim al-Razi and other teachers, such as Abu Zur'ah al-Razi. It is important that studies on ‘ilal al-ḥadīṡ continue to be developed because discussions on this topic are still rare. Kitab ‘Ilal al-Ḥadīṡ karya Ibn Abi Ḥatim adalah salah satu kitab rujukan yang banyak diperbincangkan oleh para pengkaji hadis. Penelitian ini fokus untuk menelaah dan menganalisis metodologi yang digunakan oleh Ibn Abi Ḥatim dalam kitab tersebut. Penelitian ini adalah penelitian kualitatif deskriptif. Data diperoleh dan dihimpun dari berbagai sumber, terutama Kitab ‘Ilal al-Ḥadīṡ sendiri serta buku dan artikel ilmiah lainnya yang relevan. Seluruh data yang diperoleh ditelaah dan dianalisis menggunakan pendekatan analisis konten untuk selanjutnya diambil kesimpulan. Hasil penelitian ini mendapati bahwa Ibn Abi Ḥatim termasuk ulama besar abad ke-4 yang memiliki kontribusi signifikan dalam banyak bidang ilmu keislaman. Kitab ‘Ilal al-Ḥadīṡ adalah salah satu karya monumental Ibn Abi Ḥatim yang menjadi rujukan penting para pengkaji hadis. Penelitian ini juga mendapati bahwa jumlah hadis yang menjadi objek kajian dalam kitab tersebut adalah sebanyak 2840 hadis. Ibn Abi Ḥatim tidak hanya berpegang kepada pendapat pribadi dalam menganalisis illat hadis tetapi juga merujuk kepada pendapat ayahnya Abu Ḥatim al-Razi dan guru-gurunya yang lain, seperti Abu Zur'ah al-Razi. Kajian terhadap ‘ilal al-ḥadīṡ penting terus dikembangkan karena pembahasan tentang topik tersebut masih termasuk langka.